(untitled) (Journal of Medicine, 2011)
Intractable Temporal Lobe Epilepsy may be due to Mesial Temporal Sclerosis (MTS), tumors [i.e. low grade glioma, Arterio-venous Malformation (AVM) etc], trauma, infection (Tuberculosis) etc. Intractable Temporal Lobe Epilepsy (TLE) from Mesial Temporal Sclerosis (MTS) is usually resistant to antiepileptic drugs and surgery is the treatment of choice like other form of TLE . MTS is the most common cause of intractable epilepsy in adult. Here we report three cases of surgically treated TLE that were due to MTS in the department of neurosurgery, Dhaka Medical College Hospital and a private Hospital, Dhaka, Bangladesh from August 2009 to February 2010. In all cases the only presenting symptoms was complex partial seizure (Psychomotor epilepsy) for which all underwent scalp EEG (Electro Encephalogram) and MRI (Magnetic Resonance Imaging) of Brain. All patients were managed by amygdalohippocampectomy plus standard anterior lobectomy. All patients are seizure and disease free till last follow up. Keyword: Intractable temporal lobe epilepsy; Mesial temporal sclerosis; Microneurosurgical management; Amygdalohippocampectomy. DOI: 10.3329/jom.v12i1.6934 J Medicine 2011; 12 : 61-65